Effects of Different Nitrogen Forms on Growth, Phenolic Content, and Antioxidant Activity in Hedychium speciosum and H. coronarium - Muenrew, Janjira; Suksathan, Ratchuporn; Puangpradab, Ratchadawan; Rachkeeree, Apinya; Kantadoung, Kuttiga (Naresuan University Journal: Science and Technology (NUJST); Vol 29 No 2 (2021): April-June 2021, 2020)
Nitrogen (N) is the most important nutrient element for plant growth and the synthesis of many secondary metabolites.  Plants typically obtain inorganic N in form of NH 4 + and NO 3 - . Two Hedychium species were grown in nutrient solutions modified from Smart and Barko (1985). The experiment consists of three N forms; NH 4 + , NH 4 + NO 3 - , NO 3 - and control (no N form)  with the same concentration of nitrogen (500 µM) for 60 days. Destructive sampling was done and morphology was recorded. Total phenolic content (TPC) was evaluated by Folin-Ciocalteu method while the antioxidant activity was evaluated by DPPH and ABTS radical scavenging activity. Different nitrogen forms have significantly (p ≤0.05) affected plant height, root numbers, root number and total biomass between two Hedychium species. H. speciosum had height new shoot, leaf number, root number and total biomass in NH 4 + supply. H. coronarium had height, leaf number, root number and total biomass in NH 4 + NO 3 - supply. Total phenolic contents both species were increased by NH 4 + supply. H. speciosum were accumulate total phenolic content in the leaves 21.55 mg.g -1 GAE was lower than in H. coronarium  43.49 mg.g -1 GAE, but in stem of the  H. speciosum were accumulate total phenolic content 25.08 mg.g -1 GAE was lower than in H. coronarium 20.66 mg.g -1 GAE.  NH 4 + supply increased antioxidant activity with DPPH radical scavenging activity and ABTS radical scavenging activity. Keywords: Phenolic content, Antioxidant activity, Nitrogen forms, Hedychium species, Growth, Morphology